Synergistic interaction between topical application of allicin and quercetin enhances diabetic wound healing via inflammatory in wistar rats - Nusantoro, Agik Priyo; Kuntaman, Kuntaman; Perdanakusuma, David Sontani (Penerbit Universiti Kebangsaan Malaysia, 2024)
Prolonged and excessive inflammatory processes at the wound site result in delayed healing of diabetic wounds. Allicin and quercetin have significantly inhibited tumor necrosis factor alpha (TNF-α) and increased levels of transforming growth factor beta (TGF-β) and vascular endothelial growth factor (VEGF) in rats. However, there is no known investigation on the combination of both compounds on TNF-α, TGF-β, and VEGF as a topical healing agent via inflammatory mechanisms. This study aims to determine the synergistic interaction between topical application of allicin and quercetin in enhancing diabetic wound healing via inflammatory in Wistar rats. A total of 45 male Wistar rats weighing 180-250 g were induced diabetes by a single intraperitoneal injection of streptozotocin (45 mg/kg bw). Diabetic rats underwent wound creation under anaesthesia and a square-shaped open excision wound was made with a full-thickness measurement of 1 cm × 1 cm on the right side of the rat’s back. Rats were randomly allocated into group namely, vehicle control, allicin, quercetin, and a combination of allicin and quercetin which is applied topically once a day at a dose of 10 mg/mL for 7 days. Our finding showed that once daily topical application of allicin and quercetin, both independently and synergistically, increased levels of TGF-β and VEGF, as well as decreased levels of TNF-α of the rat diabetic wound model compared with the vehicle control group over 7th day. The synergistic effects of allicin and quercetin significantly enhanced diabetic wound healing via inflammation in rats, by suppressing inflammatory cytokines and stimulating growth factors hence offering a new window of an experimental study.